Determinants of Attitudes Toward Green Product and Purchase Intention of Zero-Waste Product: A Case Study of Menstrual Cup - Agustinus Februadi; Amanda Nabilah; Moh Farid Najib (Politeknik Negeri Bandung, 2022)
Waste, currently, is one of the biggest concerns in Indonesia. As one of the solutions, innovation in the zero-waste product can help in reducing waste because it can be used repeatedly. A menstrual cup is one of zero waste products that substitute conventional sanitary napkins. However, the use of menstrual cups in Indonesia is still taboo. This study aims to determine the effect of attitudes towards green products on the purchase intention of menstrual cup products based on the factors that influence it. The data are taken from 295 Indonesian women who know about menstrual cup products through online questionnaires. The data analysis process is carried out using the SEM-PLS method with several supporting applications. The results showed that environmental attitudes, perceived health benefits, perceived value, and e-wom attitudes influenced the desire of having environmentally friendly products and increased the willingness to pay and purchase intentions for menstrual cup products.